Analisis Kemampuan Komunikasi Matematis Siswa Melalui Model Pembelajaran Kooperatif Tipe Tsts - Hana Yulandari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
According to (Aufa, 2016: 232) Mathematics is one of the subjects taught at every level of education, from early childhood education to higher education. Mathematics is also a science that underlies the development of science and technology, so that mathematics is seen as a structured and integrated science, the study of patterns and relationships, and the science of thinking to understand the world around us. From the explanation of Ansari and Aufa, it can be concluded that mathematics is one of the subjects taught in every education which is useful for helping to clarify and simplify abstract situations through language and mathematical ideas so that it makes it easier to understand problem solving that exists in everyday life.